Investigation of Boron Thermal Diffusion from Atmospheric Pressure Chemical Vapor Deposited Boron Silicate Glass for N-Type Solar Cell Process Application - Ikuo Kurachi; Kentaro Yoshioka (International Journal of Photoenergy)
An atmospheric pressure chemical vapor deposition (AP-CVD) system has been newly developed for boron silicate glass (BSG) film deposition dedicating to solar cell manufacturing. Using the system, thermal boron diffusion from the BSG film is investigated and confirmed in terms of process stability for surface property before BSG deposition and BSG thickness. No degradation in carrier lifetime is also confirmed. A boron diffusion simulator has been newly developed and demonstrated for optimization of this process. Then, the boron thermal diffusion from AP-CVD BSG is considered to be the suitable method for N-type silicon solar cell manufacturing.